Nutritional Content of Mixed Silage Pennisetum purpureum and Sesbania grandiflora With Different Additive Fermentations - Yanuarianto, Oscar; Dilaga, Syamsul Hidayat; Amin, Muhamad; Dahlanuddin, Dahlanuddin; Noersidiq, Azhary; Almatini, Soviliana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Forage consisting of grass and legumes is an important aspect of ruminant but availability is often dependent on the rainy season so preservation technology is needed, namely silage. This study aimed to determine the nutritional content of silage made from a mixture of Pennisetum purpureum and Sesbania grandiflora with different doses of fermentation additives. A Completely Randomized Design (CRD) was used, consisting of four treatments with five replications. They were P0: (75% Pennisetum purpureum + 25% Sesbania grandiflora), P1: (75% Pennisetum purpureum + 25% Sesbania grandiflora + 0.1% additive), P2: (75% Pennisetum purpureum + 25% Sesbania grandiflora + 0.2% additive), P3: (75% Pennisetum purpureum + 25% Sesbania grandiflora + 0.3% additive). Each treatment was added 2% molasses and incubated for 21 days. The results showed that the addition of fermentation additives had no significant effect (P>0.05) on DM and OM content but had a highly significant effect (P<0.01) on increasing CP, EE, and TDN content and reducing CF content. The highest average DM and OM values were observed in P0 (21.02% and 89.27%, respectively), while the highest average increases in CP, EE, and TDN were found in P3 (15.31%, 2.85%, and 50.32%, respectively), and the greatest reduction in CF was also recorded in P3 (27.89%).